2016
DOI: 10.1155/2016/6937980
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine Responses over the Entire Clinical-Immunological Spectrum of HumanLeishmania (L.) infantum chagasiInfection

Abstract: The clinical-immunological spectrum of human Leishmania (L.) infantum chagasi infection in Amazonian Brazil was recently reviewed based on clinical, DTH, and IFAT (IgG) evaluations that identified five profiles: three asymptomatic (asymptomatic infection, AI; subclinical resistant infection, SRI; and indeterminate initial infection, III) and two symptomatic (symptomatic infection, SI; American visceral leishmaniasis, AVL; and subclinical oligosymptomatic infection, SOI). TNF-α, IL-4, IL-6, and IL-10 serum cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In agreement with our results around the levels of IFN‐γ, it has been reported that in human VL, the response is predominantly Th2‐type with absence of PBMCs derived IFN‐γ 37 . However, other studies reported significant up‐regulation of IFN‐γ, TNF‐α, 38,39 IL‐1β 40 and IL‐33 41 in the sera of the patients with active VL. This discrepancy may be due to the differences in the age, ethnic and racial diversity and the species of Lesihmania as well as the sample size.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In agreement with our results around the levels of IFN‐γ, it has been reported that in human VL, the response is predominantly Th2‐type with absence of PBMCs derived IFN‐γ 37 . However, other studies reported significant up‐regulation of IFN‐γ, TNF‐α, 38,39 IL‐1β 40 and IL‐33 41 in the sera of the patients with active VL. This discrepancy may be due to the differences in the age, ethnic and racial diversity and the species of Lesihmania as well as the sample size.…”
Section: Discussionmentioning
confidence: 81%
“…In agreement with our results around the levels of IFN-γ, it has been reported that in human VL, the response is predominantly Th2-type with absence of PBMCs derived IFN-γ. 37 However, other studies reported significant up-regulation of IFN-γ, TNF-α, 38,39 IL-1β 40 and IL-33 41 To Our study has some limitations such as lower sample size, lack of determining parasite burden during treatment and long-term follow-up to determine VL recurrence.…”
Section: F I G U R Ementioning
confidence: 84%
“…In contrast, IL-6 deficient C57BL/6 mice were able to control the infection by L. major as the wild type corresponding mice (Moskowitz et al, 1997). Furthermore, multiple studies have shown a correlation between the high level of some cytokines, including IL-6, and the severity of visceral leishmaniasis (Ansari et al, 2006; Van Den Bogaart et al, 2014; Dos Santos et al, 2016; Ramos et al, 2016) and cutaneous leishmaniasis (Latifynia et al, 2012; Espir et al, 2014). To our knowledge, this is the first study addressing the determination of IL-6 protein levels produced by human neutrophils after exposure to Leishmania species.…”
Section: Discussionmentioning
confidence: 99%
“…Because IL-4 plays a crucial role in VL susceptibility and progression [30] and is involved in the regulation of IFN-γ production, its absence has a positive effect on the progression from subclinical disease to spontaneously resolved infection [8]. In our study period, IL-4 levels increased in previously infected individuals.…”
Section: Plos Onementioning
confidence: 72%
“…The mechanisms by which asymptomatic individuals can contain parasite multiplication and control infection remain unknown [3,8]. In terms of parasite control, only the joint effect of cytokines, but not their isolated effects, could be evaluated in the present study, but the results suggest that infection control may involve a balance between IL-17 and IL-10.…”
Section: Discussionmentioning
confidence: 92%